Effect of Debt Policy And Company Performance With Leverage As Moderation - Sari, Tyasha Ayu Melynda; Oktaviani, Marista; Setiawan, Adhar Putra (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
This research aims to determine the role of leverage as a moderating variable in the influence of debt policy on company performance. This research uses quantitative methods with secondary data obtained from the Indonesia Stock Exchange website and the company's official website. The population in this research is food and beverage companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021. Panel data regression analysis testing uses STATA 17. The analytical method used is multiple regression analysis (MRA). The results of this research show that: 1) Debt policy has a negative effect on company performance. Excessive use of debt causes an increase in the company's risk in generating profits and will cause shareholders to doubt the company's ability to pay the debt that has been given. This shows that the higher the debt a company has with a large amount of debt, the higher the company's risk will be and this will result in decreased financial performance, because higher debt will cause financial distress. 2) Leverage weakens the relationship between debt policy and company performance. Leverage weakens the influence of the negative relationship, which shows that the DOL functions well in mitigating the negative impact of debt policy on company performance so that the negative influence of debt policy on company performance can be reduced or weakened